Actividades turísticas y su aporte al desarrollo comunitario en el balneario Aguas Blancas en el cantón Buena Fe - Troya Intriago, Nohelia Thalia (2021)
The Buena Fe canton is located in the north of the province of Los Rios, it is one of the closest points of access to the central highlands of the country, its climate is efficient for a livestock and agricultural culture, in addition to having community spaces of wide social and economic importance. "Aguas Blancas", located in the Buena Fe canton, is one of the examples of endemic tourist attractions that, due to the lack of local tourist projection, in addition to a clear lack of mobility infrastructure in the areas of local tourist interest, leads to the abandonment of these activities or, in turn, only a very low segment of the population and tourists visit these areas of interest. In Ecuador, the Ministry of Tourism is the regulating entity that promotes national tourism activities with potential and access for international tourists. This research project seeks to generate a social and economic x-ray of the activities to be developed in the "Aguas Blancas" resort, its development and points to improve in order to attract internal and external tourists.